2019
DOI: 10.3390/rs11070794
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Remote Sensing, Machine Learning, and Citizen Science in Dutch Archaeological Prospection

Abstract: Although the history of automated archaeological object detection in remotely sensed data is short, progress and emerging trends are evident. Among them, the shift from rule-based approaches towards machine learning methods is, at the moment, the cause for high expectations, even though basic problems, such as the lack of suitable archaeological training data are only beginning to be addressed. In a case study in the central Netherlands, we are currently developing novel methods for multi-class archaeological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 73 publications
0
107
0
Order By: Relevance
“…As further automatic identification of larger areas can produce numerous points of interest, a natural next step for research in surface feature detection is to include citizen science for ground-truthing, as demonstrated by a recent Dutch study [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As further automatic identification of larger areas can produce numerous points of interest, a natural next step for research in surface feature detection is to include citizen science for ground-truthing, as demonstrated by a recent Dutch study [63].…”
Section: Discussionmentioning
confidence: 99%
“…Automatic feature detection approaches for archaeology are a rapidly and fast developing field in archaeological prospection [60][61][62]. Recent studies have demonstrated machine learning methods for detecting a wide variety of features, including burial mounds, charcoal kilns, buildings, and field systems [10,[63][64][65][66].…”
Section: Evaluating Our Approachmentioning
confidence: 99%
“…Since mound-like archaeological features are a wide-spread and relatively homogenous phenomenon, archaeological landscapes with mounds are an ideal case for semi-automated and automated methods of classification and detection. Such methods were specifically applied with LiDAR-derived digital elevation models based on convolutional neural networks for identifying Neolithic mounds [13,14], and object-based approaches to find earthen mounds and shell heaps [15]. Other approaches used high-resolution optical satellite data, like Ikonos-2, and applied a random forests algorithm [16] or developed a training dataset for a neural network based on Google Earth images [17].…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has sought to replace rule-based automated detection with machine learning-based approaches that instead begin with a large training sample of sites and allow for a more flexible set of criteria defining what constitutes a "site" to be iteratively established (Lambers, Verschoof-van der Vaart, and Bourgeois 2019; Zingman et al 2016). While such approaches have promise, they remain in early stages of development, and are often hamstrung by the complexity and inconsistency of archaeological site databases upon which they are intended to be built (e.g., Lambers, Verschoof-van der Vaart, and Bourgeois 2019;Sadr 2016). Despite the effort being devoted to development of automated and machine-learning approaches to identification of archaeological sites and features in remotely sensed imagery, nearly all of these studies produce a large number of false positives as well as missing many known sites, and cannot yet outperform trained human analysts in terms of accuracy.…”
Section: Automated Site Detectionmentioning
confidence: 99%